(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article gives the reasons for its occurrence, structures the process of obtaining income outside the tax environment of Ukraine. Types of income and rates are described, definition of tax resident status is provided. The main provisions of international agreements, which taxpayers need to pay attention to, are presented, namely, types of activities and income, a list of taxes, their rates, and the presence of special conditions for their application. An important aspect of the study is the criteria for determining residency, including the period of residence in the country, the center of vital interests, business registration, and real estate acquisition. The article also provides an example of salary taxation by a resident of Ukraine, provided such income is generated in Lithuania, tax rates are given, the amount of taxes is calculated, and the process of crediting taxes withheld by a tax agent, declaring income, and paying the tax difference is detailed. The article also structures the process of declaring income received abroad, defines the sphere of professional interests of the consultant. Consultants for the specified type of activity can provide general consultations, check the reporting prepared by the taxpayer and provide a full range of services, which includes the calculation of the amount of income, the preparation of a tax declaration on property and income and further support, correspondence with the State Tax Service of Ukraine.